EDUKASI PELAKSANAAN TRIAGE TERHADAP TINGKAT PENGETAHUAN KELUARGA PASIEN DI IGD RS ADI HUSADA KAPASARI - Suroso, Heri; Tjokro, Silvia Haniwijaya; Apriliana, Bella; Fauziyah, Febrike Inggit; Hartanto, Mey Vina Wirianti; Qomariah, Siti Nur (Community Development in Health Journal, 2023)
Introduction & Aim: The Emergency Department (ED) is one of the spearheads of hospital health services aimed at providing first aid for patients. Providing emergency services to reduce morbidity and mortality rates it requires the ability of nurses to sort out patients who need help first, this sorting is called Triage. This community service aims to provide education on the implementation of triage on the level of knowledge of the patient's family in the ED. Method of Activity: Implementation of community service at the ED of Adi Husada Kapasari Hospital, January 2023, the target is the patient's family. The method of providing education on the implementation of triage to the patient's family is with lectures and media leaflets. The first stage collects the patient's family and gives a questionnaire sheet. The second stage is the delivery of material and discussion of questions and answers about the implementation of triage, as well as giving questionnaires. Results: A total of 10 representatives of the patient's family members participated. Characteristics based on age showed that half (50%) were aged 36-45 years, based on gender the majority (60%) were female, and based on education the majority (80%) had high school/vocational high school education. Knowledge of the patient's family before being given triage education showed that most (60%) had less knowledge, whereas after being given triage education most (60%) had good knowledge about triage. Discussion: Providing education on the implementation of triage to the patient's family is very useful, and has proven to be able to provide information as well as understanding regarding health service procedures in the ED, families better understand the actions given to their family members while in the ED, and can change the behavior and perceptions of the patient's family towards the procedure given by ED health workers.